2019
DOI: 10.3390/ijms20235977
|View full text |Cite
|
Sign up to set email alerts
|

The Role of SINE-VNTR-Alu (SVA) Retrotransposons in Shaping the Human Genome

Abstract: Retrotransposons can alter the regulation of genes both transcriptionally and post-transcriptionally, through mechanisms such as binding transcription factors and alternative splicing of transcripts. SINE-VNTR-Alu (SVA) retrotransposons are the most recently evolved class of retrotransposable elements, found solely in primates, including humans. SVAs are preferentially found at genic, high GC loci, and have been termed “mobile CpG islands”. We hypothesise that the ability of SVAs to mobilise, and their non-ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…Nevertheless, co-expression of TRPV1 and TRPV3 is found in many human tissues, which is not true of mouse tissues (e.g., DRG) which have been shown to express TRPV1 but not TRPV3 ( Figure 2 C). These functional data lend support to the hypothesis that SVAs serve as newly evolved CREs in primate genomes and contribute to gene regulation in primate species [ 13 , 14 , 17 , 26 ]. When we compared the ratio of TRPV1:TRPV3 expression between unedited and homozygous ΔSVA clones, a greater decrease in TRPV3 expression compared to TRPV1 was observed.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Nevertheless, co-expression of TRPV1 and TRPV3 is found in many human tissues, which is not true of mouse tissues (e.g., DRG) which have been shown to express TRPV1 but not TRPV3 ( Figure 2 C). These functional data lend support to the hypothesis that SVAs serve as newly evolved CREs in primate genomes and contribute to gene regulation in primate species [ 13 , 14 , 17 , 26 ]. When we compared the ratio of TRPV1:TRPV3 expression between unedited and homozygous ΔSVA clones, a greater decrease in TRPV3 expression compared to TRPV1 was observed.…”
Section: Discussionsupporting
confidence: 68%
“…We and others have previously demonstrated that SVAs preferentially insert into gene dense regions and several regions across the human genome are enriched for SVA insertions [ 17 ]. One such region previously identified was a 1 Mb region (chr17:3000001–4000000, hg19) on chromosome 17 (chr17p13.2), which contained six SVA insertions ( Figure 1 B).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SVAs harbour a variable number of tandem repeats (VNTRs) and hijack L1 retrotransposition machinery for their mobilisation. With the youngest SVA family (SVA_F), around three million years old (myo), SVA elements represent the youngest TE in the human genome [ 14 ]. In contrast, the mouse genome appears to contain cohorts of ERVs and L1s capable of retrotransposition [ 15 , 16 ].…”
Section: Gene Regulation By Transposable Elements: the Newmentioning
confidence: 99%